Severe ARDS due to Influenza A (H1N1) pdm09 Infection During Pregnancy Followed by Intrauterine Fetal Death at Alka Hospital, Lalitpur - Shrestha, Gentle Sunder; Bhuju, A; Manandhar, DN; Sharma, N (Birat Journal of Health Sciences, 2017)
Pandemic due to Influenza A (H1N1) pdm 09 has been a significant cause of morbidity and mortality worldwide. Pregnant women are at risk of severe disease and ARDS, with rapid progression of disease. There is increased risk of fetal loss. Little evidence exists regarding the management of ARDS in pregnancy. Here we report a case of H1N1 virus infection in a pregnant woman in third trimester complicated by severe ARDS and intra-uterine fetal death. Fetus was successfully expelled using vaginal Misoprostol, which was followed by improvement in oxygenation indices. However, the patient died of refractory hypotension. Influenza vaccination in the high risk population may be invaluable. Birat Journal of Health Sciences Vol.2/No.1/Issue 2/ Jan - April 2017, Page: 227-229